CONTENT OF THE PROFESSIONALLY IMPORTANT QUALITIES FOR THE SPECIALISTS AND STUDENTS OF CRAFTS SCHOOLS MAJORING IN TECHNICIANELECTRONIST (GYMNASIUM, 2010)
In the present production, the electronic industry pertains to the most important branches of thepresent economy. Also, the physical and professional-applicative training of the students of the specialitytechnical professional schools, at the conceptual-educational level, is presented only through the generalstatements, reflected in "School Curricula for Senior High Schools" (2006), which "apply also in the 12thgrade - technological field, progressive qualification route through the arts and crafts schools + additionalyear".The practice of high school teaching in the technical-electronic field demonstrates that in this field,up until now, the issues related to the specification of the content and of the physical education organizationprocess have yet many issues unsolved.